Benefits of Home-Based Exercise Training Following Critical SARS-CoV-2 Infection: A Case Report - Longobardi, Igor; Prado, Danilo Marcelo Leite do; Goessler, Karla Fabiana; Oliveira Júnior, Gersiel Nascimento de; de Andrade, Danieli Castro Oliveira; Gualano, Bruno; Roschel, Hamilton (Frontiers in Sports and Active Living, 2022)
In the current scenario, in which an elevated number of COVID-19 survivors present with severe physical deconditioning, exercise intolerance, persistent symptoms, and other post-acute consequences, effective rehabilitation strategies are of utmost relevance. In this study, we report for the first time the effect of home-based exercise training in a survivor patient from critical COVID-19 illness. A 67-yr-old woman who had critical COVID-19 disease [71 days of hospitalization, 49 of which in the intensive care unit (ICU) with invasive mechanical ventilation due to respiratory failure] underwent a 10-wk home-based exercise training aimed at recovering overall physical condition. Before and after the intervention, we assessed cardiopulmonary parameters, skeletal muscle strength and functionality, fatigue severity, and self-reported persistent symptoms. At baseline (3 months after discharge), she presented with severe impairment in cardiorespiratory functional capacity (<50% age predicted VO2peak). After the intervention, remarkable improvements in VO2peak (∆: 45.9%), oxygen uptake efficiency slope (OUES; ∆: 30.1%), HR/VO2 slope (∆: -43.5%), the lowest VE/VCO2 ratio (∆: -7.1%), and exertional dyspnea were observed. In addition, handgrip strength (∆: 22.7%), 30-second Sit-to-Stand (30-STS; ∆:14.3%), Timed-Up-&-Go (TUG; ∆: -15%) performance and Post-COVID Functional Status (PCFS) score (4 vs. 2) were also improved from baseline to post-intervention. Self-reported persistent symptoms were also improved, and Fatigue Severity Scale (FSS) score decreased (4 vs. 2.7) from baseline to post-intervention. This is the first evidence that a semi-supervised, home-based exercise training program may be safe and potentially effective in improving cardiorespiratory and physical functionality in COVID-19 survivors. Controlled studies are warranted to confirm these findings.